Education Clusters: The Ukrainian Context - Khmara, M. (Наука та наукознавство, 2015)
The study aims at theoretical and methodological grounding of the role of education clusters in economic development and analysis of their impact on competitiveness enhancement of national education systems, with emphasis on Ukraine. A review of theoretical approaches to interpretati on and definition of the notion “education cluster” is made. Information about entities that may be incorporated in education cluster, objectives and expected results of education clusters is given; their advantages compared with traditional education system and their significance in the regional context are shown. Examples of education clusters and research and education clusters currently operating in Ukraine are given.